Pendidikan Islam Multikultural Pascakonflik di Luwu Utara - Abdul Muin Razmal; Muhammad Yaumi; Rusdiansyah Rusdiansyah (Institut Agama Islam Negeri Palopo, 2020)
The results showed that the post-conflict Multicultural Islamic Education that took place in North Luwu seemed to emphasize religious moral values, such as compassion, love, help, respect for differences of opinion, respect for diversity of beliefs, and other attitudes that can create relationships. harmony between faith and culture. Multicultural education instilled in students is awareness of living in cultural diversity in society, respect for human rights, and efforts to minimize prejudice, especially interreligious prejudice that has been built up in North Luwu. All of these achievements are aimed at enlivening a harmonious society in terms of ethnic, religious and cultural diversity. In its implementation, the multicultural paradigm of religious education in North Luwu allows students to appreciate plurality and heterogeneity as well as the consequences of cultural, ethnic, sectarian and religious diversity which are the reality of the North Luwu community. The post-conflict Islamic education model in North Luwu consists of three models, namely through educational institutions both public schools and Islamic institutions, through mass and political organizations, and through Islamic organizations.